2023
DOI: 10.1029/2022gl101733
|View full text |Cite
|
Sign up to set email alerts
|

Can Unleveed Agricultural Fields in Deltas Keep Pace With Sea‐Level Rise?

Abstract: Many tropical and subtropical deltas are densely populated centers of agriculture that are threatened by sea-level rise (SLR). Local SLR can be amplified by anthropogenic activities that enhance land-surface subsidence, such as damming, fluid extraction, coastal deforestation, and levee or polder construction (Syvitski et al., 2009). Often, these alterations to the landscape are driven by the need to expand agriculture and aquaculture, and local stakeholders must balance economic stability against future decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…However, there is a weak surface uplift signal in the new land area of the estuary, which is mainly due to the continuous siltation of large amounts of sediment brought by the upper Yellow River [74]. A recent study has also shown that in the Ayeyarwady Delta, Myanmar, unleveed agricultural fields in deltas are less vulnerable to subsidence than leveed or poldered fields [75]. As a result, the rich wetland vegetation in the Yellow River estuary, such as Suaeda sala, Tamarix chinensis, Spartina alterniflora, Phragmites australis, can help capture sediment in a similar way to mangroves or crops, making levee land less likely to sink than levee land.…”
Section: B Uncertainties Of Subsidence and Demmentioning
confidence: 99%
“…However, there is a weak surface uplift signal in the new land area of the estuary, which is mainly due to the continuous siltation of large amounts of sediment brought by the upper Yellow River [74]. A recent study has also shown that in the Ayeyarwady Delta, Myanmar, unleveed agricultural fields in deltas are less vulnerable to subsidence than leveed or poldered fields [75]. As a result, the rich wetland vegetation in the Yellow River estuary, such as Suaeda sala, Tamarix chinensis, Spartina alterniflora, Phragmites australis, can help capture sediment in a similar way to mangroves or crops, making levee land less likely to sink than levee land.…”
Section: B Uncertainties Of Subsidence and Demmentioning
confidence: 99%
“…A related, widespread source of confusion is associated with the interplay between deposition and subsidence. For example, studies of river delta vulnerability have implied that a reduction of sediment supply increases subsidence (e.g., Becker et al, 2020;Glover et al, 2023). However, the opposite is true: vertical accretion and subsidence from compaction in the upper portion of the sediment column are closely coupled (Saintilan et al, 2022) due to the effective stress exerted by newly accumulated sediment (Zoccarato and Da Lio, 2021).…”
mentioning
confidence: 99%
“…A related, widespread misconception is associated with the interplay between deposition and subsidence. For example, studies of river delta vulnerability have implied that a reduction of sediment supply increases subsidence (e.g., Becker et al 2020;Glover et al 2023). However, the opposite is true: vertical accretion and subsidence from compaction in the upper portion of the sediment column are closely coupled (Saintilan et al 2022) due to the effective stress exerted by newly accumulated sediment (Zoccarato and Da Lio 2021).…”
mentioning
confidence: 99%